(untitled) (Journal of the College of Basic Education, 2022)
Search to get to know: An educational tutorial knowledge based on McCarthy’s model in learning some academic wrestling grips. Research to Recognize: Preparing Tutorial Modules McCarthy’s Model in Learning Some Curriculum Wrestling Holds. Learn about the impact of educational units according to the McCarthy model. Learn some wrestling grips. In light of the research objectives, the researcher puts the following hypotheses. There is a positive effect between the pre and posttests of the research sample in learning some wrestling grips. The experimental method was used, and the research sample was selected from the second stage students in the Department of Physical Education and Sports Sciences, College of Basic Education, Al-Mustansiriyah University.